Daily lives and daily routines in the long eighteenth century - Andersson, Gudrun 1962-; Stobart, Jon 1966- (Routledge Studies in Eighteenth-Century Cultures and Societies, 2021)
"This book explores the ways in which the lives and routines of a wide range of people across different parts of Europe and the wider world were structured and played out through everyday practices. It focuses on the detail of individual lives and how these were shaped by spaces and places, by movement and material culture - both the buildings they occupied and the objects they used in their everyday lives. Drawing on original research by a range of established and emerging scholars, each chapter peers into the lives of people from various social groups as they went about their daily lives, from citizens on the streets to aristocrats at home in their country houses, and from the urban elite at leisure to seamen on board ships bound for the East Indies. For all these people, daily routines were important in structuring their lives, giving them a rhythm that was knowable and meaningful in its temporal regularity, be that daily, weekly or seasonal. So too were their everyday encounters and relationships with other people, within and beyond the home; these shaped their practices, movements and identities, and thus served to mould society in a broader sense"--